(untitled) (Journal of Scientific Research, 2025)
Molodtsov pioneered the concept of soft sets, offering a method to classify elements of a universe based on a specified set of parameters. This approach serves to model vagueness and uncertainty. Semigraphs are a generalized form of graphs introduced by Sampathkumar. The integration of soft set theory into semigraphs led to the creation of soft semigraphs. Due to its adeptness in handling parameterization, the field of soft semi-graph theory is rapidly evolving. This study introduces AND and OR operations within soft semi-graphs and explores some of their characteristics. Furthermore, we present various soft semi-graph measurements, such as distance, radius, diameter, and center.